Qualitative Analysis of Students’ Misconceptions on Energy Conservation in Mechanical Systems - Utama, Rodika; Kusumaningtyas, Dian Artha; Toifur, Moh.; Mustava, Oki; Salamah, Asnin Nur (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
Energy conservation is a fundamental principle in physics, yet numerous studies report that students often hold misconceptions regarding its meaning and application. This study aims to qualitatively explore senior high school students’ misconceptions about the conservation of energy in mechanical systems. Data were collected from 36 students in grades X and XI using a four-tier diagnostic test combined with semi-structured interviews. Thematic analysis was employed to identify the types and patterns of misconceptions. Results indicate that students frequently perceive energy as a consumable entity that disappears during processes involving friction, or equate kinetic energy directly with force. Other misconceptions include the belief that energy can be permanently lost in non-conservative systems and that potential energy does not exist unless motion occurs. These findings highlight persistent gaps in conceptual understanding despite formal instruction. The study suggests that explicit teaching strategies, such as conceptual change approaches and multiple representations, are required to address these alternative conceptions.